(NsILXNYE ZEMLETRQSENIQ uZBEKISTANA W (B1984-1985 (NGG(B. :s ((N|PICENTRALXNYE NABL@DENIQ(B, (NZAPISI(B, (NSPEKTRY(B) /s - (NsOKOLOW(B, (Nw(B.(N`(B.s; (NfREMD(B, (Nw(B.(Nm(B.s; (N~ERNOW(B, (N`(B.(Nk(B.s; (N{TEJNBERG(B, (Nw(B.(Nw(B.s ((NmOSKWA (B:s (NnAUKA(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 36-37 (16 (NNAZW(B.)s
Keywords: (NgEOFIZIKAs; (NzEMLETRQSENIQs; (NuZBEKSKAQ sss